(untitled) (Global Journal of Human-Social Science, 2012)
This paper explores the benefits and entitlements due to members of three Nigerian migrant associations in Accra, Ghana. In doing this, the paper first attempts (retracing Nigerian presence in Ghana, and then discusses recent developments in Nigerian migration to Ghana. In the discussion on Nigerian migrant associations in Accra, Ghana, two specific issues are highlighted, namely, the profiles/activities of the associations and the benefits and entitlements due to association members and leaders. The discussions on the benefits and entitlements are grounded within the social capital framework. A number of conclusions have been reached based on the evidence of the empirical data.